Heavy metals characterization of sludge from a recycling paper mill in the Philippines - Carrillo, Lorraine A. (Animo Repository, 2003)
Sludge and wastewater are the two most urgent environmental problems confronting the industry of pulp and papermaking. Wastewater treatment sludge is the largest volume residual waste stream generated by the pulp and paper industry. The disposal of sludge in developed countries includes composting paper mill sludge. Composting the sludge is an alternative method proposed by the ARRPET-DLSU Minor Issue Group. The Department of Agriculture's (DA) standards for organic fertilizer's maximum allowable content of heavy metals provided the legislative regulation for the conversion of sludge to compost. Determination of the C/N ratio of the sludge is an estimate of the composting quality of the sludge. This study makes an analysis of sludge from a Philippine paper mill to establish whether the sludge might contain the heavy metals cadmium, chromium, lead, mercury, nickel and zinc. The research is designed to characterize the sludge of a specific paper-recycling mill in the Philippines so as to assess the possibility of sludge conversion as soil amendments or as compost. The research presented three discharge points established as the sampling points. Research shows that the metal content of the sludge vary from point to point but is highest during the production of white paper. The metals chromium, mercury and nickel are non-detectable in all samples at all three discharge points for the four weeks of sampling. Composting of the sludge also requires nitrogen amendments since the C/N ratio of the sludge is very high at 156:1. The optimum C/N ratio for compost is 30:1. These metal contents are compared to the US EPA Part 503 and the Department of Agriculture's guidelines for organic fertilizers and composts to ensure that the sludge does not contain any contaminants in toxic amounts. The sludge results are very low compared to these standards leading to the conclusion that composting of the sludge is a feasible alternative technology for recycling paper mill sludge.